Early cardiovascular protection by initial two-drug fixed-dose combination treatment vs. monotherapy in hypertension. (27th July 2018) - Rea, Federico; Corrao, Giovanni; Merlino, Luca; Mancia, Giuseppe
Abstract: Aims: Guidelines support use of drug combinations in most hypertensive patients, and recently treatment initiation with two drugs has been also recommended. However, limited evidence is available on whether this leads to greater cardiovascular (CV) protection compared to initial monotherapy. Methods and results: Using the healthcare utilization database of the Lombardy Region (Italy), the 44 534 residents of the region (age 40–80 years) who in 2010 started treatment with one antihypertensive drug ( n  = 37 078) or a two-drug fixed-dose combination (FDC, n  = 7456) were followed for 1 year after treatment initiation to compare the risk of hospitalization for CV disease associated with the two treatment strategies. To limit the confounding associated with non-randomized between-group comparisons, data were also analysed by: (i) matching the two groups by the high-dimensional propensity score (HDPS) and (ii) comparing, in patients experiencing one or more CV events ( n  = 2212), the CV event incidence during subperiods in which patients were prescribed mono- or FDC therapy (self-controlled case series design). Compared to initial monotherapy, patients on initial FDC therapy showed a reduced 1 year risk of hospitalization for any CV event (−21%, P  < 0.01). This was the case also when groups were compared according to the HDPS analysis (−15%, P  < 0.05). Finally, in patients experiencing CV events, the event incidence was much less when, during the 1 year follow-up, they were under FDC therapy than under monotherapy (−56%, P  < 0.01). The reduced risk of hospitalization was always significant for ischaemic heart disease and new onset atrial fibrillation, and included hospitalization for cerebrovascular disease and heart failure when monotherapy and FDC therapy were compared within patients. Conclusion: In a real-life setting, a comparison of the incidence of early CV events during antihypertensive monotherapy and FDC shows that the latter strategy leads to a more effective CV protection. This scores in favour of a two-drug FDC strategy as first step in the hypertensive population.